Comparative Review On Earthquake Mitigation And Preparedness Policy In Indonesia - Hafidzy, Aldyan; Suraya, Anna; Nebbia, Rebecca (Direktorat Penelitian, Pengabdian Masyarakat, Dan Kerjasama Universitas Binawan (DPPMK Universitas Binawan), 2025)
This research is done by reviewing the earthquake mitigation policy in Indonesia and then making a comparison to certain countries that are also prone to earthquake disasters. The countries that are used as comparison subjects are Japan and the United States because both countries have their share of similarities and differences with Indonesia that can be reviewed in the comparison. The earthquake mitigation policy in Indonesia doesn’t have a strong function as an enforceable policy. Most policies in Indonesia in terms of earthquake mitigation and disaster management only function as guidance and standards. Indonesia also has a long way to go in developing the earthquake mitigation system, as the policy was first introduced in 2007 as part of the 2007 Disaster Management Act. Japan implemented a proactive uniform earthquake mitigation policy, with the prime target being the building code and regulation. Another initiative is implementing a retrofitting program that targets old and already existing buildings to make them more earthquake-resistant. The United States implemented a varied policy in each state in terms of earthquake mitigation systems. Most earthquake mitigation policies are implemented in earthquake-prone states such as California. Nevertheless, the earthquake mitigation policy in the United States also has an enforceable function, with the prime target being the building code and the retrofitting program. This research explores gaps in Indonesia's earthquake mitigation and preparedness systems and holds significant value as a foundation for future research on earthquake mitigation systems in Indonesia.